GREEN SYNTHESIS OF Fe3O4 NANOPARTICLES USING Spinacia oleracea Lin. LEAF EXTRACT AND ITS EFFECT IN FEED ENRICHMENT IN Catla catla FISH FINGERLINGS - UMAMAHESWARI, M.; KRISHNAMURTHY, R.; ELUMALAI, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Iron oxide nanoparticles (IONPs) have gained considerable attention because of their unique physicochemical properties. In the present study, IONPs were successfully green synthesized using leaf extract of Spinacia oleracea as an eco-friendly and straightforward method to evaluate their potentiality in increasing and improving the growth of organisms in aquaculture. This leaf extract was used as the reducing agent in green synthesis of IONP’s. FESEM-EDS characterized these nanoparticles(NP) were found to have the size range of 55 to 250 nm. The EDS study of NP’s identified various elements (C, O, Al, Si, K, Co, S, Cl, K, Ca and Fe) with its composition. The Fe NPs synthesized from spinach extract has an estimated percentage of 40.01% iron .The quantitative analysis of iron content present in the sample was estimated by Atomic absorption spectroscopy. The experiment was conducted with five different concentrations i.e., Control, FeNPs10, Fe-NPs20, Fe-NPs30, Fe-NPs40 and Fe-NPs50 each with three replications. Fishes were fed twice a day with a feeding rate of 3% body weight. Blood serum was analyzed for total proteins, cholesterol and triglyceride level. The reagents used for are of analytical grade and pure. For the present investigation Catla catla [C. catla] fish fingerlings has been selected. The aquarium water quality parameters like temperature, pH, dissolved oxygen and ammonia were recorded and calculated.